Cinema as a Mirror: Analysing Racial Conflicts in Agathe Cléry - Narcis, Stéphane (Global Journal of Cultural Studies, 2023)
This academic article delves into the intricate portrayal of racial conflicts in the film Agathe Cléry. This analysis contributes to our broader understanding of how visual media shapes societal perceptions of race and ethnicity by critically examining how cinema represents racial tensions. It engages with critical theories on racial identity, racism, and multiculturalism to illuminate the film’s social significance. Taking a multidisciplinary approach, this article offers new insights into the evolving dynamics of racial conflicts in contemporary society. It explores the enduring relevance of cinematic narratives in challenging prevailing notions of racial identity and discrimination, aligning with and extending the work of scholars who have explored the impact of media on societal attitudes and behaviours. This study serves as a synthesis of film analysis and sociological perspectives. It not only dissects the complexities of human interactions as depicted in Agathe Cléry but also highlights the transformative potential of cinema as a tool for promoting inclusive narratives and addressing pressing social issues. Through this analysis, we gain a deeper appreciation of how cinema can initiate meaningful conversations about social problems, challenge preconceived notions, and foster tolerance. It invites viewers to critically engage with racial prejudices, encouraging them to strive for a more inclusive and equitable society. This article underscores the decisive role of cinema in challenging societal norms and fostering essential discussions on racial identity and discrimination. It reflects on the significance of authentic representation, avoiding stereotypes, collaboration with experts, and promoting dialogue within the film industry. It suggests future research directions, including audience reception studies, comparative analyses of films from diverse cultural contexts, investigations into the long-term effects of anti-racist films, and explorations of intersectionality in film. Agathe Cléry is a compelling example of cinema’s ability to address social problems, challenge preconceived notions, and foster tolerance. This article comprehensively analyses the film within the context of racial conflicts, emphasising the importance of authentic representation and responsible storytelling. As the film industry evolves, embracing these recommendations and exploring future research directions will contribute to a cinema that reflects our diverse world and actively engages in the ongoing journey toward social justice and equity.